Efficient energy transfer via the cyanide bridge in dinuclear complexes containing Ru(ii) polypyridine moieties - Cadranel, Alejandro (2012)
We report the synthesis, structure and properties of the cyanide-bridged dinuclear complex ions [Ru(L)-(bpy)(μ-NC)M(CN)5]2−/− (L = tpy, 2,2′;6′,2′′-terpyridine, or tpm, tris(1-pyrazolyl)methane, bpy = 2,2′- bipyridine, M = Fe(II), Fe(III), Cr(III)) and the related monomers [Ru(L)(bpy)X]2+ (X = CN− and NCS−).All the monomeric compounds are weak MLCT emitters (λ = 650?715 nm, ϕ ≈ 10−4). In the Fe(II) and Cr(III) dinuclear systems, the cyanide bridge promotes efﬁcient energy transfer between the Ru-centered MLCT state and a Fe(II)- or Cr(III)-centered d?d state, which results either in a complete quenching of luminescence or in a narrow red emission (λ ≈ 820 nm, ϕ ≈ 10−3) respectively. In the case of Fe(III) dinuclear systems, an electron transfer quenching process is also likely to occur.